Behavioral health risk factor profiles in general hospital patients: identifying the need for screening and brief intervention - Jennis Freyer-Adam; Florian Noetzel; Sophie Baumann; Ali Alexander Aghdassi; Ulrike Siewert-Markus; Beate Gaertner; Ulrich John (BMC, 2019)
Abstract Background Little is known about the clustering of behavioral health risk factors (HRFs), namely the occurrence of 16 specific combinations of tobacco smoking, at-risk alcohol use, overweight and physical inactivity in general hospital patients. Furthermore, social inequalities in HRFs, health and life expectancy are a major concern in public health. In order to establish the need for screening and intervention in general hospital care, the study aimed to determine the co-occurrence of HRFs in patients in four medical departments, and to investigate differences by gender, age and socio-economic characteristics. Methods Over 17 months, a systematic multiple HRF screening was conducted at one general hospital in northeastern Germany. In total, 6251 18-64 year old patients (92% of eligibles) participated. Proportions and confidence intervals were calculated for all 16 HRF profiles stratified by department, gender, age group, school education, and employment status. Results In total, 92.2% of the participants (58.6% male) reported ≥1 HRF, and 65.7% ≥2 HRFs. Men (71.2%), patients aged 35-49 (67.9%) and 50-64 years (69.5%), lower educated (79.0%), and unemployed (77.8%) patients had larger proportions of ≥2 HRFs than their counterparts. In all departments, the most common HRF profiles included overweight. HRF profiles that included alcohol and/ or smoking were more common in ear-nose-throat and trauma surgery than in internal medicine and general surgery patients. Men had higher rates concerning almost all HRF profiles including ≥2 HRFs and alcohol; women concerning profiles that included ≤2 HRFs and inactivity. In older patients, profiles with ≥2 HRFs including overweight; and in younger patients, profiles with smoking and/or alcohol were more common. In lower educated patients, profiles with ≥2 HRFs including inactivity; and in higher educated patients profiles with ≤2 HRFs including alcohol were more common. Compared to others, unemployed patients had higher rates of profiles with ≥3 HRFs including smoking. Conclusions Two in three patients require interventions targeting two or more HRFs. The findings help to develop screening and brief intervention for patients with specific health risk profiles, that can reach most patients, including those most in need and those most hard to reach, with socio-economically disadvantaged people in particular. Registry clinicaltrials.gov: NCT01291693.